The Experiences and Perspectives of Basic Sciences Faculty Members of Medical School of Tehran University of Medical Sciences Regard to Different Teaching Metho - Mitra Sarshar; kamran Soltani Arabshahi; Leila Jouybari; Fatemeh Mehravar; Nader Momtazmanesh; Akram Sanagu; Gholamreza Hasanzadeh (Development Strategies in Medical Education, 2014)
Introduction: Researches has shown that one of the important keys to learning "teaching method" and the impact of other factors such as teacher characteristics on student learning are minimal. So in recent years, medical education has undergone tremendous changes and has developed a variety of new methods of teaching.  The purpose of this study was to explore the experiences and perspectives of basic sciences faculty members of medical school of Tehran university of medical sciences regard to different teaching methods. Methods: In this qualitative study in 2013, using purposeful sampling, thirty faculty members from different academic rank, degree, school and training records participated in the research. The data gathered by In-depth interviews. All of the interviews tape recorded transcribed verbatim and analyzed according to the content analysis method. Results: The main themes taken from the study "method of teaching", "Choosing and applying various methods of teaching" and "Barriers and facilitators of teaching methods" are. Different ways of teaching among teachers in three general categories: traditional techniques, new methods, techniques and fusion categories were merged. Choosing and using different teaching methods, teaching time in this study can be school supplies, teacher's personality and interest rates, he pointed to the proper functioning of the system and the education system. Conclusion: These results indicate that despite the fact that most science teachers agreed with the implementation modern methods of education, but due to the lack of suitable substrates and administrative obstacles, the methods to graduate students at has been considered more appropriate. Furthermore, this study showed that teachers and students are prepared for transformation and modernization of medical education. Development actors in the educational system need to be able to think well, a good theory should be able to argue a new theory and practice in the field to operate.